Social Determinants of Mental Health in Organizations - Hurtado Olga Lucia, Montoya; Patiño Karent Valentina, Martinez (International Journal of Psychosocial Rehabilitation, 2020)
Mental health is structured through the interaction between interinstitutional, intercultural, and intersectoral systems that translate into social determinants of health. The World Health Organization mentions some such as social inclusion, lack of discrimination, violence, economic participation, health systems, society, community, relationships, and individuals; it is important to take into account from the actions as individual or collective the analysis of these determinants as a strategy for the decision-making from the primary care of the mental health. It presents a qualitative investigation that made the contextualization and analysis of the contents of documents with respect to three theoretical supports (social determinants, mental health, and organizations); then an analysis of the discourse of Semiestrucutadas interviews was carried out with people with knowledge on the subject in order to analyze the perspective that different professions have on the mentioned and finally, triangulation of the information was made where the purpose of the discussion was to generate awareness in the readers about the importance of the social determinants of mental health in organizations.